Potential Production of Carbon Gases and Their Responses to Paleoclimate Conditions: An Example From Xiaolongtan Basin, Southeast Tibetan Plateau - Wang, Gen; Wang, Yongli; Wei, Zhifu; Sun, Zepeng; He, Wei; Ma, Xueyun (Frontiers in Earth Science, 2021)
Uplift of the Tibetan Plateau plays a significant and lasting role in the variations of climate conditions and global carbon cycle. However, our knowledge is limited due to the lack of long-sequence records revealing rates of CO2 and CH4 production, hampering our understanding of the relationship between paleoclimatic conditions, carbon cycling and greenhouse gas flux. Here, we present a combination of paleoclimate records and low-temperature thermal simulation results from sediments of the Xiaolongtan Basin at the southeastern margin of the Qinghai-Tibetan Plateau, spanning the late Miocene (14.1~11.6 Ma). The n-alkane-derived proxies suggested that the sources of organic matter were obviously different: a mixed source including lower organisms and terrestrial higher plants for the Dongshengqiao Formation from 14.1 to 12.6 Ma, and a predominant contribution from terrestrial higher plants for Xiaolongtan Formation between 12.6 and 11.6 Ma. The paleoclimate was generally warm and humid as reflected by the lipid biomarkers, consistent with previous studies. In addition, the carbon gases (including CO2 and hydrocarbon gases) generated by the low-temperature thermal simulation experiments indicated a production rate of CO2 and CH4 were as high as 88000 ml/kg rock and 4000 ml/kg rock, respectively, implying there were certain amounts of carbon gases generated and released into the atmosphere during their shallow burial stage. Besides, the calculated production rate of carbon gases and the estimated burial flux of organic carbon varied in response to the variations of paleoclimate conditions. Based on these observations, we propose that the climate conditions predominantly controlled the formation and accumulation of organic matter, which consequently affected the production of carbon gases and burial flux of organic carbon. The results presented here may provide a significant insight into the carbon cycle in the southeast of the Tibetan Plateau.